2021
DOI: 10.31703/gesr.2021(vi-ii).23
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Issue of Burn-Out of School Teachers: Looking Back, Looking Forward

Abstract: Is there any relationship between organizational culture and teacher's burnout in schools? This is a hot question asking for an answer. This research study has been conducted to explore and understand this relationship. Literature provides for a different outcomes from different studies in different settings and countries. However, majority of studies provide for and establish the relationship between organizational culture and burnout. It suggests that poor or unconducive organizational culture where there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Firstly, the external locus of control was found to have a significant positive relationship with emotional exhaustion. This aligns with past research which has repeatedly shown that teachers with a more external locus of control, meaning they believe life events are outside of their personal control, tend to experience higher levels of burnout [14,65]. For example, [14] found that an external locus of control was the strongest predictor of emotional exhaustion in their sample of Italian high school teachers.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Firstly, the external locus of control was found to have a significant positive relationship with emotional exhaustion. This aligns with past research which has repeatedly shown that teachers with a more external locus of control, meaning they believe life events are outside of their personal control, tend to experience higher levels of burnout [14,65]. For example, [14] found that an external locus of control was the strongest predictor of emotional exhaustion in their sample of Italian high school teachers.…”
Section: Discussionsupporting
confidence: 88%
“…This aligns with past research which has repeatedly shown that teachers with a more external locus of control, meaning they believe life events are outside of their personal control, tend to experience higher levels of burnout [14,65]. For example, [14] found that an external locus of control was the strongest predictor of emotional exhaustion in their sample of Italian high school teachers. They hypothesized that teachers with an external locus are more likely to appraise demands as threatening and deplete their coping resources faster.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations